Online MEMS-Based Specific Gravity Measurement for Lead-Acid Batteries - Yashwant Gulab Adhav; Dayaram Nimba Sonawane; Chetankumar Yashawant Patil (Advances in Technology Innovation, 2023)
Traditional methods for measuring the specific gravity (SG) of lead-acid batteries are offline, time-consuming, unsafe, and complicated. This study proposes an online method for the SG measurement to estimate the state-of-charge (SoC) of lead-acid batteries. This proposed method is based on an air purge system integrating with a micro electro mechanical system sensor. Through the proposed strategy, the SoC measurement achieves up to ±1% accuracy. The technique has an SG accuracy of ±0.002% which is better than the glass hydrometer accuracy of ±0.005% in the battery charge reading. The experimental results show that the high accuracy and precise measurements of SG and SoC can be conducted by using the proposed method.